A comparative study of the role of disease severity in drug reimbursement decision making in four European countries. Issue 2 (February 2015) - Franken, Margreet; Stolk, Elly; Scharringhausen, Tessa; de Boer, Anthonius; Koopmanschap, Marc
Highlights In Belgium, France, The Netherlands and Sweden disease severity is an important, mostly implicit, consideration in drug reimbursement decision making. Belgium and France explicitly use the level of severity of the disease to determine societal willingness to pay. Most policymakers prefer qualitative information on the severity of the disease. Most policymakers prefer implicitly weighing all reimbursement decision criteria.